Klinische Indikationen hochauflösender MRT-Diagnostik des peripheren Nervensystems - Godel, Tim; Weiler, Markus (Der Radiologe, 2017)
Clinical/methodical issuePeripheral neuropathies are common and diagnostically often challenging disorders. Difficulties particularly exist in lesion localization and recognition of complex spatial lesion patterns.Standard diagnostic methodsMedical history taking, neurological examination, neurophysiological tests and nerve ultrasonography represent the gold standard in the diagnosis of peripheral nerve lesions but have known methodical limitations.Methodical innovationsThe use of 3 Tesla magnetic resonance neurography (MRN) is an additional diagnostic imaging tool recently developed for the high-resolution visualization of long segments of peripheral nerves. Reasonable clinical indications for MRN are exemplarily presented.PerformanceUsing MRN a direct visualization and thus precise localization of focal and non-focal peripheral nerve lesions of various origins can be achieved with high spatial resolution down to the anatomical level of nerve fascicles.AchievementsUsing MRN large anatomical areas of the peripheral nervous system (PNS) can be covered in a single examination session, spatial nerve lesion patterns can be evaluated and the underlying causes can often be detected.Practical recommendationsThe MRN is a valuable supplement to the diagnostic work-up of the PNS, especially in cases that cannot be clarified with standard diagnostic methods. Evaluation of the spatial nerve lesion pattern gives additional information on the origin of the underlying disease. Reasonable indications for MRN are the assessment of proximal nerve structures including the brachial and lumbosacral nerve plexi, the clarification of inconclusive diagnostic results, preoperative, postoperative and posttraumatic assessments, the identification of fascicular nerve lesions and the differential diagnosis of an alleged somatoform disorder.